A rare case of spontaneous simultaneous bilateral tubal ectopic pregnancy - Shintre, Hemant; Dhanu, Vilas; Dhanu, Ranjana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Ectopic pregnancy is still an important cause of maternal mortality. The incidence of ectopic pregnancies is reported to be rising. Spontaneous bilateral tubal ectopic pregnancy in the absence of preceding induction of ovulation is extremely unusual occurrence and is the rarest form of ectopic pregnancy. The estimated incidence is 1 in 725 to 1580 of all ectopic corresponding to one per 200000 live births. The preoperative diagnosis of bilateral ectopic pregnancy remains a challenge. Serum β-hCG, TVS, color Doppler help making diagnosis of ectopic pregnancy but laparoscopy is gold standard diagnostic modality. The diagnosis of bilateral tubal pregnancy is usually made intra-operatively. This underscores the importance of identifying and closely examining both tubes at the time of surgery, even in the presence of significant adhesive disease. Salpingostomy, salpingotomy, salpingectomy, segmental resection, fimbrial expression are the operative modalities described for management of ectopic pregnancy.